KAJIAN TEORI MATEMATIKA EVERYONE IS A TEACHER HERE DAN PENDEKATAN QUANTUM TEACHING - Muntuan, Jade Rehulina (LPPM Universitas Advent Indonesia, 2018)
Mathematics is one of the subjects which is learned at all levels of education. Ithappens because mathematics is used and needed in every aspect human activity. One of theabilities students must possess is the ability to solve problems. Facts in Indonesia show thatstudents' mathematical problem-solving abilities at both secondary and tertiary educationlevels are still not high. From previous studies reported that only 35% of students had problemsolvingskills, 25% of students were able to design completion plans and 20% of students hadthe ability to solve problems. The remaining 20% are students who have the ability to lookback at the completion steps. Looking at the research reports above, the teachers are expectedto choose the right strategy to be used in carrying out the learning process in the classroom sothat the goals that have been written in the teaching plan can be achieved. A learning modelcalled